The impact of neurocysticercosis in california: a review of hospitalized cases. - Curtis Croker; Matthew Redelings; Roshan Reporter; Frank Sorvillo; Laurene Mascola; Patricia Wilkins (Public Library of Science (PLoS), 2012)
To assess the burden of neurocysticercosis (NCC) in California we examined statewide hospital discharge data for 2009. There were 304 cases hospitalized with NCC identified (incidence = 0.8 per 100,000). Cases were mostly Latino (84.9%), slightly more likely to be male than female (men 57.6%, women 42.4%) with an average age of 43.5 years. A majority of cases were hospitalized in Southern California (72.1%) and many were hospitalized in Los Angeles County (44.7%). Men were more likely than women to have severe disease including hydrocephalus (29.7% vs. 18.6%, p = 0.027), resulting in longer hospitalizations (>4 days, 48.0% vs. 32.6%, p = 0.007) that were more costly (charge>$40 thousand men = 46.9% vs. woman = 4.1%, p = 0.026). Six deaths were recorded (2.0%). The total of NCC-related hospital charges exceeded $17 million; estimated hospital costs exceeded $5 million. Neurocysticercosis causes appreciable disease and exacts a considerable economic burden in California.